Cegah Kenakalan Remaja Melalui Pendidikan Karakter - I Gede Agung Jaya Suryawan (Jurnal Penjaminan Mutu, 2016)
Adolescents as the future generation should have the character to be proud of and be a role model to the next generation. However, this time, there are not a few Indonesian adolescent learners do negative things, such as skipping school , involved in brawls , drugs , and sexual harassment . Besides harming themselves such misbehaviors are also harmful to society. All parties, namely families, schools and the community, must work together to find solutions for it. One of the things that can be done is to provide character education in the family and schools that teach children to make decisions wisely and practise it in their daily lives so that they can contribute positively to their environment.